Modes of production during the Inka Imperial Period (1420–1535 AD) and the Early Colonial Period (1535–1660 AD) in the Jujuy Valley, Argentina - Vaquer, Jose Maria (2024)
The transition between the Inka Imperial Period and the Early Colonial Period in the current territory of Argentina corresponds to the Spanish invasion and the impact it had on the native populations. The imposition of the early colonial mode of production, based on the exploitation of South American mineral resources and their export to Europe, in turn, gave rise to a series of subsidiary industries. Among them, cattle breeding, muleteering, and slaughtering to obtain dried beef occupied a prominent place since their destination was the sustenance of the mining workforce. In this work, based on historical sources and archaeological studies, we propose to interpret the relationships between landscapes, environments, territories, and human populations from the imposition of the early colonial mode of production, considering pre-Hispanic modes of production and anti-production. To do this, we focus on the dierent resistance strategies of the original populations and the advances and setbacks of the conquerors for the eective control of the territory, particularly the Jujuy Valley. The following pages do not aim to provide new data on the topic, but rather to oer a dierent analysis and approach to it.